The Effect of Storytelling and Instagram Marketing on Purchase Intention Through Brand Awareness - Hanna Banjarnahor; Onan Marakali Siregar (Journal of Business and Economics Research (JBE), 2026)
This study aims to analyze the effect of storytelling and Instagram marketing on Fore Coffee purchase intention in Medan, with brand awareness as a mediating variable. The study uses a quantitative approach with purposive sampling techniques on 100 respondents aged 18-35 years who have been exposed to Fore Coffee Instagram content. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) through SmartPLS 4.0. The results show that Instagram marketing has a significant effect on brand awareness and purchase intention, both directly and through the mediating role of brand awareness. In contrast, storytelling does not have a significant effect on brand awareness or purchase intention. The coefficient of determination (R²) values of 0.437 for brand awareness and 0.754 for purchase intention indicate that the model explains a moderate proportion of variance in brand awareness and a substantial proportion of variance in purchase intention. The results confirm that, in the context of Fore Coffee consumers in Medan, the effectiveness of digital marketing is more determined by the optimization of Instagram's visual and interactive features than by a narrative approach. These findings contribute to the digital marketing literature by highlighting the relative effectiveness of Instagram marketing and storytelling in influencing purchase intention through brand awareness. The results also provide practical insights for businesses to optimize Instagram marketing strategies.